Chinese herbal medicines for mild cognitive impairment: A protocol for meta-analysis and trial sequential analysis. Issue 39 (1st October 2021) - Gu, Si-Chun; Zhang, Li-Min; Wang, Chun-Xu; Qu, Yan-Jie; Ma, Jing-Yi; Zhen, Rong-Rong; Gu, Chao; Yuan, Can-Xing
Abstract: Background: Mild cognitive impairment (MCI), as a common neurodegenerative aging disease representing an intermediate stage between normal cognitive functioning and dementia, poses an excessive burden on health care. The clinical benefit of Chinese herbal medicines (CHMs) for MCI remains inconclusive. This study is aimed at evaluating the efficacy and acceptability of CHMs through meta-analysis and trial sequential analysis (TSA). Methods: We applied extensive strategies on preliminary literature screening to identify relevant randomized controlled trials which meticulously compare any of CHMs interventions with placebo groups as monotherapy for MCI. The primary outcome of this study is the change of global cognitive function, and the secondary outcomes include assessments of activities of daily living, mood, and adverse events. Data synthesis, risk of bias assessment, sensitivity and subgroup analyses, and TSA will be conducted with application of Review Manager, Stata, and TSA software. The quality of the evidence will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation instrument. INPLASY registration number: INPLASY202190006 (https://inplasy.com/inplasy-2021-9-0006/ ). Results: This study will confirm the clinical efficacy and safety of CHMs when used in the treatment of patients with MCI. Conclusion: This study will provide reliable evidence and references for the selection of CHMs in therapy and future clinical research of MCI.